Velocity sections of the upper mantle under the oceans - V.V. Gordienko; L.Ya. Gordienko (Геофизический журнал, 2016)
We constructed the models of the distribution of longitudinal seismic waves velocities for the upper mantle oceanic regions: mid-ocean ridges (MOR), basins, trenches, island arcs and coastal ridges, back-arc troughs (BAT). They are in line with the schemes of advection-polymorphic deepseated processes in tectonosphere. Under the island arcs and coastal ridges models meet the alpine geosyncline supplemented with recent activization. Under the MOR and BAT the models coincide. They correspond to the scheme of recent heat and mass transfer for rifting which on the mafic crust with continental thickness leads to oceanization. The basin model shows the result of smoothing of thermal anomalies under the MOR or BAT in about 50 100 million years. The trench model corresponds to the result of lateral warming-up of upper layers of the mantle of the inactive blocks from the island arc and basin